A morpho-phonological Past Tense processing as a clinical marker in SLI EFL learners. (2nd September 2017) - Even-Simkin, Elena
ABSTRACT: The clinical marker in specific language impairment (SLI) population is the subject of considerable debate. SLI is the one of the frequently diagnosed atypical language phenomena found among early school-age children (McArthur et al., 2000; Spear-Swerling, 2006). For example, children with SLI have difficulty applying the Past Tense rule to verbs, even though they can accurately repeat phonologically similar forms of the words (Hoeffner & McClelland, 1993). In this study, I discuss the grammatical deficits in the SLI population by studying the generation of both 'regular' and 'irregular' English Past Tense forms and explain how the rates of the correct use of the 'irregular' versus 'regular' form may be considered as a clinical SLI marker. This study defines the differences in the grammatical sensitivity in the EFL learners and provides additional essential insight into SLI, in general, and its identification in the EFL learners, in particular.